Economic Effects of Renewable Energy Technologies - Maradin Dario; Cerović, Ljerka; Mjeda Trina (Naše gospodarstvo/Our economy, 2017)
Rapid economic development has resulted in the more frequent use of renewable energy technologies. On the other hand, the production and use of renewables fosters the development of new technologies, creating many new opportunities for entrepreneurial-minded individuals and, consequently, the economy in general. Renewable energy technologies have a multiplier effect in spurring the economy and the development of not only the energy sector but also all the supporting activities related to such industry. The purpose of this research is to analyse both the positive and the negative economic effects of investing in various renewable technologies, as well as to confirm, by means of the energy-economy model, the benefit of such technologies in boosting the economy.